A Phase II, Randomized, Double-blind, Controlled Safety and Immunogenicity Trial of Typhoid Conjugate Vaccine in Children Under 2 Years of Age in Ouagadougou, Burkina Faso: A Methods Paper. (7th March 2019) - Laurens, Matthew B; Sirima, Sodiomon B; Rotrosen, Elizabeth T; Siribie, Mohamadou; Tiono, Alfred; Ouedraogo, Alphonse; Liang, Yuanyuan; Jamka, Leslie P; Kotloff, Karen L; Neuzil, Kathleen M
Abstract: The recent Typhoid Fever Surveillance in Africa Program demonstrated an overall adjusted incidence of typhoid fever 2–3 times higher than previous estimates in Africa. Recently, a single-dose typhoid conjugate vaccine that allows infants as young as 6 months old to be vaccinated was prequalified by the World Health Organization (WHO). This Vi-based conjugate vaccine demonstrated robust immunogenicity after 1 dose in infants and children 6 through 23 months of age in India with no safety signal, and is currently being tested for the first time on the African continent in Malawi. The WHO Strategic Advisory Group of Experts recommends studies to evaluate co-administering Vi-typhoid conjugate vaccine (Vi-TCV) with routine childhood vaccines in typhoid-endemic countries. The Burkina Faso immunization schedule includes yellow fever vaccine (YFV) at 9 months and meningococcal A conjugate vaccine (MCV-A) at 15 months, in addition to measles-rubella vaccine at both 9 and 15 months. Co-administration testing of Vi-TCV with these routine vaccinations will provide the data needed to support large-scale uptake of Vi-TCV in sub-Saharan Africa. A randomized, controlled, Phase II trial of Vi-TCV co-administration with the vaccinations routinely given at 9 and 15 months of age is planned in Burkina Faso. The overall aim is to assess the safety and immunogenicity of Vi-TCV when co-administered with YFV at 9 months of age and with MCV-A at 15 months of age. A total of 250 participants (100 infants aged 9–11 months and 150 children aged 15–23 months) will be enrolled. Clinical Trials Registration. NCT03614533.